Gold nanoparticles for vectorization of nucleic acids for cancer therapeutics - Ferreira, Daniela (2020)
Cancer remains a complex medical challenge and one of the leading causes of death worldwide. Nanomedicines have been proposed as innovative platforms to tackle these complex diseases, where the combination of several treatment strategies might enhance therapy success. Among these nanomedicines, nanoparticle mediated delivery of nucleic acids has been put forward as key instrument to modulate gene expression, be it targeted gene silencing, interference RNA mechanisms and/or gene edition. These novel delivery systems have strongly relied on nanoparticles and, in particular, gold nanoparticles (AuNPs) have paved the way for efficient delivery systems due to the possibility to fine-tune their size, shape and surface properties, coupled to the ease of functionalization with different biomolecules. Herein, we shall address the different molecular tools for modulation of expression of oncogenes and tumor suppressor genes and discuss the state-of-the-art of AuNP functionalization for nucleic acid delivery both in vitro and in vivo models. Furthermore, we shall highlight the clinical applications of these spherical AuNP based conjugates for gene delivery, current challenges, and future perspectives in nanomedicine.